One‐year clinical and echocardiographic outcomes of direct implantation of a self‐expanding valve. Issue 3 (12th November 2020) - Benetos, Georgios; Karmpalioti, Maria; Drakopoulou, Maria; Stathogiannis, Konstantinos; Xanthopoulou, Maria; Latsios, George; Synetos, Andreas; Bei, Evangelia; Voudris, Vassilis; Iakovou, Ioannis; Katsimagklis, Georgios; Moraitis, Sotiris; et al.
Abstract: Objective: To present 1 year clinical and echocardiographic outcomes of the randomized DIRECT (Pre‐dilatation in Transcatheter Aortic Valve Implantation Trial) trial. Background: Intermediate‐term data from randomized studies investigating the safety and efficacy of direct implantation are lacking. Methods: DIRECT trial randomized 171 consecutive patients with severe aortic stenosis at four tertiary centers to undergo TAVI with the use of self‐expanding prostheses with (pre‐BAV) or without pre‐dilatation (no‐BAV). The primary endpoint was device success according to the VARC‐2 criteria. All patients underwent a clinical and echocardiographic follow‐up at 1 year. All‐cause and cardiac mortality, stroke, heart failure hospitalization, and new pacemaker implantation were recorded. Results: At 1 year, four deaths were recorded in pre‐BAV group (4.7%) and three deaths in no‐BAV group (3.5%). There was no difference in Kaplan–Meier plots between the two groups in all‐cause mortality at 1 year (log‐rank p  = .72). Similarly, there was no difference in the incidence of permanent pacemaker implantation between the two groups at 1 year (27/67–40.3% in no‐BAV group versus 20/69–29% in pre‐BAV group, log‐rank p  = .24). There was no significant difference between pre‐BAV and no BAV group in aortic valve area (1.84 ± 0.39 cm 2 vs. 1.85 ± 0.44 cm 2, p  = .90), mean aortic valve gradient (8.36 ± 5.04 vs. 8.00 ± 4.04 mmHg, p  = .65) and moderate or severe paravalvular regurgitation (5–6.6 vs. 4–5.7%, respectively) at 1 year. The same applied independently from the performance of post‐dilatation at baseline. Conclusions: Direct, without pre‐dilatation, implantation of a self‐expanding valve has no impact on one‐year clinical and echocardiographic outcomes, independently also from the baseline performance of post‐dilatation.